2013
DOI: 10.1590/s0100-83582013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Germination ecology of Rhynchosia capitata: an emerging summer weed in Asia

Abstract: -Rhynchosia capitata is becoming an increasing problem in summer crops, such as cotton, soybean, pearl millet and mungbean in many Asian countries. Laboratory and greenhouse studies have been conducted to determine the effects of several environmental factors on seed germination patterns and seedling emergence of R. capitata. We investigated whether the diverse ecological factors such as temperature, light, salinity, moisture stress, pH, and soil depth affected germination and seedling emergence of R. capitata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Delayed emergence might be due to the production of the phenolic compound vanillic acid, which has inhibitory effect on germination (Ali et al, 2013). Although emergence was delayed with the decomposition period of 30 days, it occurred much earlier than the 15-day decomposition period.…”
Section: Resultsmentioning
confidence: 99%
“…Delayed emergence might be due to the production of the phenolic compound vanillic acid, which has inhibitory effect on germination (Ali et al, 2013). Although emergence was delayed with the decomposition period of 30 days, it occurred much earlier than the 15-day decomposition period.…”
Section: Resultsmentioning
confidence: 99%
“…A falta de algum desses fatores pode fazer com que a germinação ocorra de forma lenta e em menor escala, ou ainda, induzir à dormência (Canossa et al, 2008). Temperatura e luz são considerados os sinais ambientais que regulam a germinação, distribuição das espécies e interações ecológicas (Ali et al, 2013), quando a umidade do solo é suficiente para embebição da semente, pois a água faz parte das estruturas moleculares como proteínas e ácidos nucleicos, bem como de lipídeos e carboidratos (Guimarães et al, 2008).…”
Section: Fatores Ambientais Que Influenciam O Fluxo De Emergênciaunclassified
“…Also, studying the ecology of seed germination of various species is very useful to recognize and explain plant evolution and ecological adaptation (Baskin et al, 2004). Biological and ecological information, specifically germination ecology of a specific weeds is necessary to develop long-term management strategies (Mennan and Ngouajio, 2006;Nakamura and Hossain, 2009;Ali et al, 2013;Tanveer et al, 2014). Peters et al (2000) reported that knowledge of the influence of environmental factors on the germination and emergence behavior of seeds would be helpful to prevent their invasion to new areas and determine its management practices.…”
Section: Introductionmentioning
confidence: 99%